3D Behavior of Schottky Barriers of 2D Transition-Metal Dichalcogenides - Yuzheng Guo (ACS Applied Materials & Interfaces, 2015)
The transition metal dichalcogenides (TMDs) are two-dimensional layered solids with van der Waals bonding between layers. We calculate their Schottky barrier heights (SBHs) using supercell models and density functional theory. It is found that the SBHs without defects are quite strongly pinned, with a pinning factor S of about S = 0.3, a similar value for both top and edge contact geometries. This arises because there is direct bonding between the contact metal atoms and the TMD chalcogen atoms, for both top and edge contact geometries, despite the weak interlayer bonding in the isolated materials. The Schottky barriers largely follow the metal induced gap state (MIGS) model, like those of three-dimensional semiconductors, despite the bonding in the TMDs being largely constrained within the layers. The pinning energies are found to be lower in the gap for edge contact geometries than for top contact geometries, which might be used to obtain p-type contacts on MoS2.